The Relationship Between Self-Esteem and Mental Health Among Students of the Faculty of Teacher Training and Education, Guidance and Counseling Study Program, Tadulako University - Munifatun Nisa M. Yahya; Dhevy Puswiartika; Munifah Munifah; Hasan Hasan (Journal of Educational Sciences, 2026)
This study aims to determine the level of self-esteem among students, describe the condition of students’ mental health, and analyze the relationship between self-esteem and mental health among students of the Guidance and Counseling Study Program at Tadulako University. This research employed a quantitative approach with a correlational design, using a survey method through questionnaires that had been tested for validity and reliability. Data analysis techniques included descriptive analysis and Pearson Product Moment correlation test. The results showed that students’ self-esteem levels were in the moderate to high category, while their mental health condition was relatively good, although some students still experienced psychological problems. The Pearson correlation test revealed a significant relationship between self-esteem and mental health, with a correlation coefficient (r) of -0.665 and a significance value of 0.000 (p < 0.05), as well as a coefficient of determination (R²) of 0.442, indicating a contribution of 44.2%. The study concludes that there is a significant relationship between self-esteem and mental health among students, where higher self-esteem is associated with lower levels of mental health problems.